Efficiency, Efficacy, and Power in the Implementation of a Medication Adherence Aid - Roy Cherian (Health Literacy Research and Practice, 2018)
Nonadherence to medication regimens is common, with approximately 50% of patients not taking their medications as prescribed. The Universal Medication Schedule (UMS) is a set of standardized, evidence-based, and patient-centered instructions for pill-form medications that has demonstrated improvements in adherence by promoting patient comprehension. An urban, publicly funded, integrated health care system attempted to adopt UMS labeling but had limited success at its largest pilot site, which was a safety-net health care system's outpatient pharmacy. To assess barriers to implementation, we engaged pharmacists at this site in group interviews. We thematically analyzed transcripts by integrating sociological work on standardization with grounded theory methodologies. In addition to lacking technological infrastructure, tensions among efficiency, efficacy, and effectiveness, and tension between individual/biomedical versus population health perspectives emerged as barriers to implementation. Additionally, we discovered that hierarchies of professional power impeded uptake. For successful implementation of evidence-based practices for vulnerable populations in resource-poor settings, efforts must anticipate and reconcile the tensions among conflicting demands, professional hierarchies, and divergent orientations to patient care.